2016
DOI: 10.1007/s00167-016-4070-9
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical effects of graft rotation on ACL reconstruction tunnel mismatch

Abstract: Rotating the patellar tendon is an efficient method for shortening a relatively long graft; however, more biomechanical studies are necessary to recommend this technique in clinical practice owing to the resulting decrease in graft stiffness that could compromise knee stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…On the other hand, according to a study by Kim et al [19] twisting or braiding hamstring tendons decreased the failure load and graft stiffness. A recent study using porcine patella tendon grafts that studied graft rotations up to 900° found that rotation did not change graft strength but did have an effect on elastic modulus [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, according to a study by Kim et al [19] twisting or braiding hamstring tendons decreased the failure load and graft stiffness. A recent study using porcine patella tendon grafts that studied graft rotations up to 900° found that rotation did not change graft strength but did have an effect on elastic modulus [24].…”
Section: Discussionmentioning
confidence: 99%
“…Arnold et al [2] found in patients that a 180° degree internal and external rotation had an unpredictable effect on the maximal force of ACL graft. A recent study that examined the use of large graft rotations, up to 900°, to shorten grafts, found that with a porcine patella tendon rotation reduced the modulus of elasticity, but did not affect strength [24]. In summary, many of the prior studies that have examined graft twisting in regard to altering mechanical strength of the graft and those that considered the effect on knee kinematics have found inconclusive or differing results.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also acknowledge that long-term effects on graft remodeling and revascularization are still unknown. Subsequently, de Olivero et al 40 assessed 40 porcine ligaments at larger degrees of rotation. Progressive graft shortening occurred up to 720°, with no effect on ultimate load to failure found at 540, 720, or 900°.…”
Section: Graft Manipulationmentioning
confidence: 99%